2015
DOI: 10.1111/jep.12403
|View full text |Cite
|
Sign up to set email alerts
|

Medication reconciliation at admission to surgical departments

Abstract: There was a high prevalence of REs among patients admitted to the surgical departments, most frequently the omission of a drug. The risk of an RE was higher in patients admitted for elective versus emergency surgery, as well as with the receipt of a larger number of drugs before admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
1
13
0
5
Order By: Relevance
“…Our percentage is similar to the percentage found by González-García et al 12 who reported that 55.1% of reconciliation errors required the participation of a pharmacist for their resolution in the Orthopaedic Surgery and Traumatology Department and the Angiology and Vascular Surgery Department. This could be explained by the greater experience medical specialists have with chronic medication compared with surgeons.…”
Section: Discussionsupporting
confidence: 90%
“…Our percentage is similar to the percentage found by González-García et al 12 who reported that 55.1% of reconciliation errors required the participation of a pharmacist for their resolution in the Orthopaedic Surgery and Traumatology Department and the Angiology and Vascular Surgery Department. This could be explained by the greater experience medical specialists have with chronic medication compared with surgeons.…”
Section: Discussionsupporting
confidence: 90%
“…The most common reconciliation error was drug omission 5. Data from our review show that, following the establishment of the protocol for elective surgery patients at our institution, only 24 patients had a reconciliation error.…”
Section: Discussionmentioning
confidence: 87%
“…Most patients who are going to undergo elective surgery take medication that is not related to the surgery and therefore this raises safety issues which need to be addressed to reduce potential complications during the perioperative period 5. The present study shows the benefits of a proactive MR protocol (figure 1) conducted by a hospital pharmacist prior to patient admission, which ensures surgeons have the right information about the patient’s home medication when they have to prescribe hospital treatment in the operating theatre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the findings in this study number of medications is widely found as risk factor for medication errors in transitions of care Number of medications is a very obvious risk factor for medication errors; the more medication a patient uses, the higher the risk of errors.…”
Section: Discussionmentioning
confidence: 99%